Functionally redundant control of cardiac hypertrophic signaling by inositol 1, 4, 5-trisphosphate receptors. (November 2017) - Garcia, M. Iveth; Karlstaedt, Anja; Chen, Jessica J.; Amione-Guerra, Javier; Youker, Keith A.; Taegtmeyer, Heinrich; Boehning, Darren
Abstract: Calcium plays an integral role to many cellular processes including contraction, energy metabolism, gene expression, and cell death. The inositol 1, 4, 5-trisphosphate receptor (IP3 R) is a calcium channel expressed in cardiac tissue. There are three IP3 R isoforms encoded by separate genes. In the heart, the IP3 R-2 isoform is reported to being most predominant with regards to expression levels and functional significance. The functional roles of IP3 R-1 and IP3 R-3 in the heart are essentially unexplored despite measureable expression levels. Here we show that all three IP3 Rs isoforms are expressed in both neonatal and adult rat ventricular cardiomyocytes, and in human heart tissue. The three IP3 R proteins are expressed throughout the cardiomyocyte sarcoplasmic reticulum. Using isoform specific siRNA, we found that expression of all three IP3 R isoforms are required for hypertrophic signaling downstream of endothelin-1 stimulation. Mechanistically, IP3 Rs specifically contribute to activation of the hypertrophic program by mediating the positive inotropic effects of endothelin-1 and leading to downstream activation of nuclear factor of activated T-cells. Our findings highlight previously unidentified functions for IP3 R isoforms in the heart with specific implications for hypertrophic signaling in animal models and in human disease. Highlights: All three IP3 R isoforms are expressed in rat ventricular cardiomyocytes and in human heart tissue. All three IP3 R isoforms are required for ET-1 induced hypertrophic signaling. Calcium release induced by ET-1 is not restricted to the nuclear compartment in rat ventricular cardiomyocytes.